Role of Bicontinuous Structure in Elastomeric Electrolytes for High‐Energy Solid‐State Lithium‐Metal Batteries (Adv. Mater. 1/2023). Issue 1 (5th January 2023) - Han, Junghun; Lee, Michael J.; Lee, Kyungbin; Lee, Young Jun; Kwon, Seung Ho; Min, Ju Hong; Lee, Eunji; Lee, Wonho; Lee, Seung Woo; Kim, Bumjoon J.
Abstract : Lithium‐Metal Batteries In article number 2205194, Seung Woo Lee, Bumjoon J. Kim, and co‐workers report the structure–property–electrochemical performance relationship of an elastomeric electrolyte system, demonstrating the importance of balancing lithium‐ion transport and mechanical properties for achieving high‐energy solid‐state lithium‐metal batteries. The cover image features dendritic lithium—which disturbs the use of lithium metal—entrapped in the elastomeric electrolyte.